Process optimization for atrial fibrillation ablation. - Boehmer, Andreas A; Summ, Alena; Vila, Steffen; Rothe, Moritz; Nussbaum, Elena; Zezyk, Celine; Dobre, Bianca C; Kaess, Bernhard; Ehrlich, Joachim R (EP: Europace, 2022)
Aims: In the light of an increasing prevalence of atrial fibrillation (AF) and growing evidence for the superiority of early invasive rhythm control, the demand for ablation therapy is rising. Accordingly, ablation centres will have to maximize their capacity by either adding electrophysiology laboratory resources or optimizing process management. In order to optimize process management, we applied "Lean Six Sigma" method to a single ablation center. We compared procedural parameters, acute efficacy and safety of cryoballoon pulmonary vein isolation (cryoPVI) before and after modifications.Methods and Results: Patients (n = 713) undergoing cryoPVI (108 before and 605 after process optimization) were analysed. Within 3 years of process optimization, electrophysiology laboratory occupancy time (150.7 ± 44.4 vs. 94 ± 22.1 min, P < 0.001), procedure time (84.5 ± 21-47.4 ± 12 min, P < 0.001), left-atrial dwell time (53.9 ± 18.4-31.9 ± 9.9 min, P < 0.001), and fluoroscopy time (15.8 ± 5.1 vs. 6.2 ± 2.8 min, P < 0.001) decreased. Contrast dye use (116 ± 35 vs. 27 ± 15 mL, P < 0.001) and radiation dose (893 ± 1078 vs. 253 ± 249 cGy cm2, P < 0.001) were reduced by ∼77 and ∼72%, respectively. There was no difference in safety endpoint occurrence (3.7 vs. 1.5%, P = 0.11).Conclusion: The process optimization of cryoPVI for AF therapy using the 'Lean Six Sigma' method significantly increases efficiency without compromising patient safety.